Similarities And Differences Of English And Malay Feline Proverbs: A Conceptual Metaphor Approach - Mohamad Khairul Adilah, Siti Mukhlisa (2022)
This study aims at analysing the disparity of the feline representations with the search for their similarities and differences, as well as exploring the cross-cultural differences between English and Malay feline proverbs, with 24 and 42 proverbs respectively.